Postcard of N. Bouchonnet written to Sono Osato and Roman Jasinski, Paris - Bouchonnet, N. (1939)
MS Acc10.008 comprises the postcard from Madame N. Bouchonnet to Sono Osato and Roman Jasinski ("Jasha") advising the return of Colonel Wassily de Basil to Paris, and confirming arrangments for the 1939-1940 Australian tour of the Ballets Russes. The postcard is typed and dated October 18, 1939, at Paris (1 folder).
Manuscript reference no.: MS Acc10.008.
Keywords: Bouchonnet, N. -- Correspondence; Osato, Sono, -- 1919- -- Correspondence; Jasinski, Roman, -- 1912-1991 -- Correspondence; Basil, W. de; Ballets Russes du Col. W. de Basil; Theatrical producers and directors -- Australia; Ballet companies -- Australia; Ballet -- Australia